SEARCH FOR MEANING OF EXISTENCE IN STEVENSON'S KUNG FU PANDA (2008): AN EXISTENTIALIST PERSPECTIVE - KURNIAWAN, RISANDO (2010)
This study is about search for meaning of life in the Kung Fu Panda movie. This objective of study is to apply the existentialist theory to analyze the meaning of life in Kung Fu Panda movie based on Existentialist Perspective. In doing so, the writer uses Sartre's Theory to answer the problem of the study. The study is descriptive qualitative research whose the data are taken from script of Kung Fu Panda Movie by using methodology of literature as the references. The data collecting technique is library research, while the data analyzing technique is descriptive. The result of the study shows that: First, based on structural analysis the writer has successfully deliver the moral message through all structural elements. Each of the structural elements are interrelated to each other form and solid unity. Second based on the existential analysis the existence of human is meaningful if he declares himself in a good action, highest level transcendence of ego.